Pengaruh Struktur Pasar Terhadap Tingkat Efisiensi Perbankan Syariah - Tia Rachmawati (Tauhidinomics: Journal of Islamic Banking and Economics, 2022)
This research aims to analyze the influence of the market structure against the level of Sharia Banking efficiency. This research uses the analysis of the panel data and the selected Fixed Effect Model (FEM). The dependent variable from this research is a BOPO that becomes a level of efficiency and the independent variable is Hirschman-Herfindhal Index (IHH) as a calculation rasio to measure the market structure, as well as the control variable Return On Assets (ROA) and Non Performing Finance (NPF). The results of this research show that IHH is positive significant influential against both BOPO and simultaneous. ROA influential negatively significant both partial and simultaneous against BOPO and NPF influential positive significant both partial and simultaneous against BOPO.